Fuzzy Environmental Model for Evaluating Water Quality of Sangam Zone during Maha Kumbh 2013. (4th August 2013) - Srivastava, Pankaj; Burande, Anjali; Sharma, Neeraja
Abstract : It is a well-known fact that water is the basic need of human beings. The industrial wastes nearby rivers and several anthropogenic activities are responsible for deteriorating water quality of rivers in India. The present research paper deals with the design and development of soft computing system to assess the water quality of rivers Ganga and Yamuna during the Maha Kumbh 2013 in and around Sangam Zone, Allahabad, by making use of physicochemical parameters relationship.